2012
DOI: 10.1055/s-0032-1324800
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Software Analysis of Ultrasonographic Textures in Experimental Testicular Torsion

Abstract: In experimental testicular torsion, ischemic changes can be detected by PDUS power/angio mode using blood flow alterations as early as the second hour. Tissue damage cannot be evaluated within the first 2 hours of torsion with B-mode ETX analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Regarding the patients (n=10) with advanced but compensated liver cirrhosis, all measurements (n=30 PFA and n=30 PW-Doppler) were also applicable (median angle alpha of 14 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 degrees). The PFA and PW-Doppler showed good correlation (r=0.61, 95% CI −0.03–0.89).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the patients (n=10) with advanced but compensated liver cirrhosis, all measurements (n=30 PFA and n=30 PW-Doppler) were also applicable (median angle alpha of 14 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 degrees). The PFA and PW-Doppler showed good correlation (r=0.61, 95% CI −0.03–0.89).…”
Section: Resultsmentioning
confidence: 99%
“…1a/b demonstrates the principle of this pixel flow analysis (PFA) tool compared to the established PW-Doppler. PFA has already been evaluated for placenta vascularization, umbilical cord flow during pregnancy, and in an experimental setting to detect ischemic lesions in testicular torsion in rats, with promising results 20 21 22 23 . Furthermore, a phantom study showed a good correlation of the actual flow recorded with PFA using a plastic tube with a predefined flow volume 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the testes need to be slightly suspended because, even resting, the organ on the operating 12 and is recognized as the most accurate method for measuring testicular volume in situ 1,6 . It is a noninvasive method that allows for the diagnosis of a wide range of testicular diseases 10,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…horns, the uterine horns were removed and the right and left ovaries were seen. All measurements were taken by the same person (SBM) using a portable LOGIQ Book XP ultrasound (General Electric Healthcare, Solingen, Germany), with a 6-10 MHz linear probe in a manner that had a minimal mechanical effect on the ovaries [16]. At least 3 Power Doppler US (angio mod) images were taken for each ovary.…”
Section: Rosiglitazone Treatmentmentioning
confidence: 99%
“…Afterward, the Pixelflux program (Version 1.0, Chameleon-Software, Leipzig, Germany) was utilized to obtain dynamic tissue perfusion measurements on the Power Doppler images. The temporal variation in intensity (I) red, Vred, average intensity, and whole intensity values were statistically evaluated [16].…”
Section: Rosiglitazone Treatmentmentioning
confidence: 99%